ANALISIS PERKEMBANGAN PLTS DI PROVINSI SUMATERA SELATAN MENUJU TARGET 296,6 MW PADA TAHUN 2025 - Manurung, D.Y.; Kumara, I.N.S.; W.G. Ariastina, W.G. Ariastina; Pangaribuan, J. (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
Target capacity of Solar Power Plant in Province of South Sumatra is pursued through the construction of a rooftop PV mini-grid system with off-grid and on-grid systems. Based on National Energy General Plan (RUEN) in 2017, Province of South Sumatra has the third largest solar power potential on a national scale with a target of Solar Power Plant development reaching 296.6 MW in 2025. Province of South Sumatra is the second most populous province on Sumatra Island with electricity consumption reaching 5,308 GWh in 2020. This study tries to analyze the development of Solar Power Plant in Province of South Sumatra based on the literature review. Solar Power Plant that has been installed until 2021 reached 12.441 MW or around 4.12% of the South Sumatra RUEN target of 296.6 MW in 2025. The types of Solar Power Plant applications in Province of South Sumatra consist schools, hotels, palm oil factories, irrigation pumps , and utility networks spread across Palembang, Muara Enim Regency, Muara Rawas Regency, and Ogan Hilir Regency